Intracranial Extraskeletal Myxoid Chondrosarcoma : Case Report and Literature Review - Park, Jin Hoon (The Korean Neurosurgical Society, 2012)
Intracranial extraskeletal myxoid chondrosarcoma is extremely rare, with only seven patients previously reported. We present a case report of a 21-year-old woman admitted for weakness in her right extremities and symptoms of increased intracranial pressure. Magnetic resonance imaging (MRI) revealed hydrocephalus and a well-enhanced large mass around her left thalamus. A left parietal craniotomy and a cortisectomy at the superior parietal lobule were performed. Total surgical resection was also performed, and pathology results confirmed an extraskeletal myxoid chondrosarcoma. Postoperative MRI showed no residual tumor, and the patient underwent radiotherapy. After six months of radiotherapy, the patient's headache and weakness had improved to grade IV. This malignant tumor showed high rates of recurrence in previous reports. We here report another occurrence of this highly malignant and rare tumor in a patient treated using total surgical excision and adjuvant radiotherapy.